Barriers to an enabling environment in start-up acceleration in fragile and conflict-affected settings in Jordan and Nigeria - Ires, Idil (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The enabling environment is a critical driver of business acceleration, particularly in sectors essential for sustainable development, such as agriculture, food, and water security. In Africa and the Middle East, these sectors underpin economic stability and livelihoods, yet businesses face numerous challenges that impede their ability to scale and innovate. A supportive enabling environment—comprising policy frameworks, institutional structures, access to finance, infrastructure, and market systems—plays a decisive role in overcoming systemic barriers such as food insecurity, climate change, and resource scarcity. However, structural weaknesses, fragmented markets, limited access to capital, and governance challenges continue to hinder the scaling of sustainable enterprises in these regions.